2017
DOI: 10.1093/nar/gkx723
|View full text |Cite
|
Sign up to set email alerts
|

Abasic and oxidized ribonucleotides embedded in DNA are processed by human APE1 and not by RNase H2

Abstract: Ribonucleoside 5′-monophosphates (rNMPs) are the most common non-standard nucleotides found in DNA of eukaryotic cells, with over 100 million rNMPs transiently incorporated in the mammalian genome per cell cycle. Human ribonuclease (RNase) H2 is the principal enzyme able to cleave rNMPs in DNA. Whether RNase H2 may process abasic or oxidized rNMPs incorporated in DNA is unknown. The base excision repair (BER) pathway is mainly responsible for repairing oxidized and abasic sites into DNA. Here we show that huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 91 publications
3
58
0
Order By: Relevance
“…Conversely, the oxidation of a ribonucleotide, i.e., 8-oxo-rG, on the template DNA strongly inhibited DNA synthesis by Pols and contributed to miscoding events. Because 8-oxo-rG also could not be repaired by either RER or BER 21,22 , we hypothesized that such modification of the ribonucleotide enhances the mutagenic potential in cells. Contrary to the initial hypothesis, it seems that 8-oxo-rG did not display greater mutagenic potential than rG in WT cells (Figure 3b and c).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the oxidation of a ribonucleotide, i.e., 8-oxo-rG, on the template DNA strongly inhibited DNA synthesis by Pols and contributed to miscoding events. Because 8-oxo-rG also could not be repaired by either RER or BER 21,22 , we hypothesized that such modification of the ribonucleotide enhances the mutagenic potential in cells. Contrary to the initial hypothesis, it seems that 8-oxo-rG did not display greater mutagenic potential than rG in WT cells (Figure 3b and c).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the modified ribonucleotides could exist in DNA via the oxidation of the embedded ribonucleotide and/or the insertion of damaged rNTPs during DNA replication. Base oxidation in embedded ribonucleotide inhibits RNase H2-mediated excision repair 21,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, APE1 also plays an important role as redox effector on many transcriptional factors, such as NF-κB, HIF-1α, STAT-3, PAX8, AP-1 and p53 [23][24][25][26][27], regulating important genes involved in tumor progression. Moreover, new interesting molecular functions involved in RNA metabolism were recently discovered in our laboratory [23], including processing of damaged RNA [28], miRNAs [29] and abasic and oxidized ribonucleotides embedded in DNA [30]. The different functions of APE1 are finely modulated by expression, localization, posttranslational modifications (PTMs) [31][32][33][34][35][36] and by its protein-protein interactome, as well.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was clearly demonstrated how topoisomerase I is able to recognize and cleave single rNMPs embedded in DNA, when RNase H2 is missing (15,19). Moreover, different studies were carried out to evaluate whether base excision repair (BER) pathway could also work on rNMPs embedded in DNA (9,12,15,20). Our laboratories have recently demonstrated that although BER does not have any role in repairing rNMPs embedded in DNA, apurinic/ apyrimidinic endonuclease 1, APE1, the only AP-endonuclease of BER, acts in the removal of modified rNMPs embedded in DNA, such as ribose monophosphate abasic (both apurinic or apyrimidinic) site (rAP) and oxidized rNMP (20).…”
mentioning
confidence: 99%